The Comparison between Effect of Chloralhydrate and Diphenhydramine on Sedating for Electroencephalography - HASSANZADEH RAD, AFAGH; AMINZADEH, vahid (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Hassanzadeh A, Aminzadeh V. The Comparison between Effect of Chloralhydrate and Diphenhydramine on Sedating for Electroencephalography. Iran J Child Neurol. Autumn 2016; 10(4):25-29. Abstract Objective Electroencephalography (EEG) is the most effective diagnostic tool in distinguishing epileptic seizure. Chloral hydrate (CH) is a sedative hypnotic drug, commonly used as a method of sedation in children aged<3 yr. Furthermore, diphenhydramine (DH) is a first generation antihistaminic drug (H1 receptor blocker) with anti-cholinergic effect. In this study, we aimed to compare the effects of CH and DH on sedating for EEG. Materials & Methods This retrospective cohort study was conducted on patients’ records of aged 15-72 months undergone an EEG and required sedation. Overall, 200 children were assessed including 100 patients in group 1 (CH) and 100 patients in group 2 (DH). Data were gathered by a form including age, sex, the cause of EEG, complication, success rate, first dose success, as well as sleep and awake latency. Data were reported by descriptive statistics (mean, standard deviation, number, and percent) and analyzed by t-test and chi-square using SPSS 19. Results Totally, 113(56%) male patients with the mean age of 35.62±14.00 months participated in this study. Vomiting and agitation were the most frequent complications in CH and DH groups, respectively. Most of patients in both group indicated successful sedation. CH indicated higher rate of success by first dose toward DH. In addition, CH mentioned lower sleep latency and significant difference was noted between groups. The mean duration of awake latency was higher in DH groups which showed significant difference. Conclusion CH might be a more effective drug in comparison with the DH for sedation. According to the availability and low cost of DH, investigators are advised to perform further investigations. References 1. Marcdante K, Kliegman RM, Behrman RE, Jenson HB. Nelson essentials of pediatrics: Elsevier Health Sciences; 2010. 2. Sahyoun C, Krauss B. Clinical implications of pharmacokinetics and pharmacodynamics of procedural sedation agents in children. Curr Opin Pediatr 2012;24(2):225-32. 3. Temme J, Anderson J, Matecko S. Sedation of children for CT and MRI scanning. Radiol Technol. 1990; 61(4):283- 5. 4. Soni H. Martindale: The complete drug reference–38th edition. Nursing Standard 2014;28(47):32-.5. Gauillard J, Cheref S, Vacherontrystram M, Martin J. Chloral hydrate: a hypnotic best forgotten? Encephale 2002;28(3 Pt 1):200-4. 6. Kay GG, Berman B, Mockoviak SH, Morris CE, Reeves D, Starbuck V, et al. Initial and steady-state effects of diphenhydramine and loratadine on sedation, cognition, mood, and psychomotor performance. Arch Intern Med 1997;157(20):2350-6. 7. Roehrs T, Zwyghuizen-Doorenbos A, Roth T. Sedative effects and plasma concentrations following single doses of triazolam, diphenhydramine, ethanol and placebo. Sleep 1993;16(4):301-5. 8. Engorn B, Flerlage J. The Harriet Lane Handbook: Mobile Medicine Series, Expert Consult: Elsevier Health Sciences; 2014. 9. Malviya S, Voepel-Lewis T, Tait A, Merkel S, Tremper K, Naughton N. Depth of sedation in children undergoing computed tomography: validity and reliability of the University of Michigan Sedation Scale (UMSS). Br J Anaesth 2002;88(2):241-5. 10. Fallah R, Jalili S, Golestan M, Karbasi SA, Jarahzadeh M-H. Efficacy of chloral hydrate and promethazine for sedation during electroencephalography in children; a randomised clinical trial. Iran J Pediatr 2013;23(1):27-31. 11. Bektas O, Arıca B, Teber S, Yılmaz A, Zeybek H, Kaymak S, et al. Chloral hydrate and/or hydroxyzine for sedation in pediatric EEG recording. Brain Dev. 2014;36(2):130- 6. 12. Roach CL, Husain N, Zabinsky J, Welch E, Garg R Moderate sedation for echocardiography of preschoolers. Pediatr Cardiol 2010;31(4):469-73. 13. Fávero ML, Ponce FAS, Pio MRB, Tabith Junior A, Silva FLC. Chloral hydrate to study auditory brainstem response. Braz J Otorhinolaryngol 2010;76(4):433-6. 14. Ashrafi MR, Mohammadi M, Tafarroji J, Shabanian R, Salamati P, Zamani GR. Melatonin versus chloral hydrate for recording sleep EEG. Eur J Paediatr Neurol 2010;14(3):235-8. 15. Heistein LC, Ramaciotti C, Scott WA, Coursey M, Sheeran PW, Lemler MS. Chloral hydrate sedation for pediatric echocardiography: physiologic responses, adverse events, and risk factors. Pediatrics 2006;117(3):e434-41. 16. Cengiz M, Baysal Z, Ganidagli S. Oral sedation with midazolam and diphenhydramine compared with midazolam alone in children undergoing magnetic resonance imaging. Paediatr Anaesth 2006;16(6):621-6.